VD_FINDINFO HC / 2014 / 848 vom 10. Oktober 2014 - VD Tribunal cantonal (2014)
DÉPENS, AGENT D'AFFAIRES, DISPROPORTION, EXPULSION DE LOCATAIRE | 257d CO, 110 CPC (CH), 319 let. b ch. 2 CPC (CH), 11 TDC, 20 al. 2 TDC